On the k-error linear complexity of generalised cyclotomic sequences. (2016) - Liu, Longfei; Yang, Xiaoyuan; Du, Xiaoni; Wei, Bin
Generalised cyclotomic binary sequences are divided into Whiteman-generalised cyclotomic and Ding-generalised cyclotomic. Firstly, two classes of error generalised cyclotomic sequences with length pq over Zpq are constructed; secondly, k-error linear complexity of generalised cyclotomic sequences are considered, using the trace representation and cyclotomic theory, respectively. It is shown that k-error linear complexity of generalised cyclotomic sequences do not exceed p + q-1 which is much less than the (zero-error) linear complexity.